The Role of Kv7 Channels in Neural Plasticity and Behavior - Baculis, Brian C.; Zhang, Jiaren; Chung, Hee Jung (Frontiers in Physiology, 2020)
Activity-dependent persistent changes in neuronal intrinsic excitability and synaptic strength are widely thought to underlie learning and memory. Voltage-gated KCNQ/Kv7 potassium channels have been of great interest as the potential targets for memory disorders due to the beneficial effects of their antagonists in cognition. Importantly, de novo dominant mutations in their neuronal subunits KCNQ2/Kv7.2 and KCNQ3/Kv7.3 are associated with epilepsy and neurodevelopmental disorder characterized by developmental delay and intellectual disability. The role of Kv7 channels in neuronal excitability and epilepsy has been extensively studied. However, their functional significance in neural plasticity, learning, and memory remains largely unknown. Here, we review recent studies that support the emerging roles of Kv7 channels in intrinsic and synaptic plasticity, and their contributions to cognition and behavior.